When the Going Gets Tough, Communities Believe It's Time to Optimize and Adapt. Issue 3 (16th June 2014) - Siegel, Lenny
<x xml:space="preserve">Abstract</x> The people who live in the communities where complex groundwater sites are located are as diverse as the country itself, but those who fight for the cleanup of our groundwater recognize that total cleanup may be difficult, if not impossible, in our lifetimes. Still, as explained in a December 2013 joint letter to US EPA, we want those who are responsible for environmental protection, be they polluters, developers, or regulatory agencies, to try harder before admitting defeat. In Mountain View, California, community activists have developed criteria for the adaptive cleanup of the Moffett‐MEW Regional Plume of TCE groundwater contamination that emphasizes areas with high contaminant mass, source areas, locations that reduce the need for long‐term vapor intrusion mitigation, properties where the detectable plume encroaches on residential areas, schools, and other sensitive uses, and areas planned for reuse. In many other communities, trust is the key to developing community support for remedial strategies. Communities that are listened to tend to feel more empowered. Empowered communities tend to offer more constructive advice. Decision makers tend to listen to communities that offer constructive advice. In summary, when the cleanup going gets tough, empowered communities believe that it is time to optimize and adapt, not to give up. © 2014 Wiley Periodicals, Inc.